An Analytical Study on Lecture Method as Traditional Teaching Method of the Buddha - Medhacitto, Tri Saputra (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
Teaching method is very important element in education since it determines the quality and effectiveness of learning process. The appropriate teaching methods will enhance the effectiveness learning process and student comprehension. Many teaching methods have been introduced in modern education to address different learning needs and educational goals. Among those methods, lecture method is one of the oldest teaching methods and common for all level of education. As the religious leader and teacher, the Buddha had adopted this teaching method in delivering the teachings. This research aims to explore the lecture method as traditional teaching method of the Buddha. This research discovers the Buddha’s teaching approach in dealing with different audiences. With library approach, analyzing the data from primary sources and secondary sources, this research delves into an analytical study on the role of the Buddha as the teacher and systematic approach of lecture method he used in delivering the Dhamma. The Buddha is attributed as a teacher of humans and gods (satthā devamanussānaṃ) who teaches the Dhamma in various methods (bhagavatā anekapariyayena dhammo pakāsito). In the case of lecture method, he begins with presenting the concepts (sandassetvā), making the students understand (samādapetvā), persuading the students to study further (samuttejetvā:), and finishing the lecture in the way students happy (sampahaṅsetvā).